EC-QCL sensing system–incorporated adaptive baseline correction algorithm for simultaneous detection of multiple gas components - Song, Yushuo; Peng, Wei; Li, Zifei; Yu, Benli; Zhou, Sheng; Li, Jingsong (Microchemical journal, 2024)
[Display omitted] •An adaptive baseline correction algorithm was applied.•The differential transformation was combined with the B-Spline approximation.•An enhancement factor of 3.7 was obtained compared with polynomial fitting.•Multi-gas of NH3, O3, and CO2 are detected simultaneously using EC-QCL. In this study, we presented a multi-gas sensor developed by employing an external cavity quantum cascade laser (EC-QCL)-integrated adaptive baseline correction algorithm for the simultaneous detection of ammonia (NH3), ozone (O3), and carbon dioxide (CO2). The EC-QCL sensing system was selected due to its high wavelength resolution and wide tuning range (1033–1068 cm−1), enabling the simultaneous measurement of multi-gases. The system complexity was effectively decreased and the superimposed noise was avoided by employing an adaptive baseline correction algorithm based on differential transformation and B-Spline approximation (ADTBA), which enabled the resolution of the uneven EC-QCL baseline signals. The performance validation of the ADTBA algorithm by comparing it with the conventional polynomial fitting for detecting the spectra of NH3, O3, and CO2 showed that the former outperformed the latter. The results showed a sensitivity enhancement factor of 3.7, indicating that the newly developed algorithm can generate a high-quality gas absorption spectrum. Allan deviation analysis of the system's responsiveness revealed an averaging time of 120 s resulting in sensitivities of 1.3, 26.7, and 37.0 ppm for NH3, O3, and CO2, respectively.